Effect of Old Age Allowance on Household Food Insecurity: Evidence from Rural Nepal - Adhikari, Madan; Thapa, Gaurav (International Journal of Atharva, 2026)
Background: Food insecurity remains a persistent challenge in rural Nepal despite the country’s history of agricultural self-sufficiency. The government has implemented social safety nets, notably the old age allowance, as a key strategy to combat this issue. However, the effectiveness of such cash transfer programs in directly improving food security outcomes is not well-established. Objectives: This study aims to investigate the impact of the old age allowance on household food insecurity in rural Nepal. It also seeks to identify other key socioeconomic determinants, including agricultural engagement, livestock ownership, migration, and cooperative membership, that influence food security status. Methods: The study utilized primary data collected from a cross-sectional survey of 763 households across nine rural municipalities in five provinces of Nepal. Food insecurity was measured using the Food Insecurity Experience Scale (FIES). A logistic regression model was employed to analyze the association between receiving the old age allowance and the probability of household food insecurity, while controlling for other demographic and socioeconomic variables. Findings: The results reveal that 26.9% of sampled households experienced some level of food insecurity. The logit regression analysis shows that receiving the old age allowance significantly reduces the probability of food insecurity by 8.3 percentage points. Other significant factors include agricultural livelihood and livestock ownership, which are associated with lower food insecurity, while migration is linked to a higher probability of food insecurity. Cooperative membership also demonstrates a strong negative association with food insecurity. Conclusion: The old age allowance plays a modest but significant role in enhancing food security among rural households in Nepal. However, its effectiveness is strengthened when combined with other factors such as agricultural livelihoods, livestock assets, and cooperative participation. The findings highlight the need for a multi-sectoral approach that integrates social protection with sustainable livelihood interventions to effectively address food insecurity. Novelty: This study provides empirical evidence from a primary survey specifically quantifying the isolated impact of Nepal’s largest social safety net—the old age allowance—on household food insecurity using a validated FIES scale. It offers a nuanced analysis by contrasting its effect with other critical determinants like migration and cooperative membership within the rural Nepali context.